2022
DOI: 10.1186/s13017-022-00412-4
|View full text |Cite
|
Sign up to set email alerts
|

Motorized 2–3 wheelers death rates over a decade: a global study

Abstract: Background Motorized 2–3-wheelers-related death is high due to the exposed body of the driver/passenger and the high speed. The United Nation (UN) Decade of Action for road safety aimed to reduce road traffic deaths by 50% by the year 2020. We aimed to study the factors affecting the death rates of motorized 2–3 wheelers injured victims and whether the reduction in the death rates has met the UN target. Methods Data were retrieved from the WHO Glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A recent study [25] identified GNI, motorized two and three wheelers per person ratio, percentage of helmet-wearing rate, and the interaction between vehicle/person ratio and motorized two and three wheelers/person ratio as significant factors affecting PTW mortality rates. In another study [26], the impact of variables on injury severity differed significantly for helmet-wearing and non-helmet-wearing motorcyclists.…”
Section: Summary and Critique Of The Literaturementioning
confidence: 99%
“…A recent study [25] identified GNI, motorized two and three wheelers per person ratio, percentage of helmet-wearing rate, and the interaction between vehicle/person ratio and motorized two and three wheelers/person ratio as significant factors affecting PTW mortality rates. In another study [26], the impact of variables on injury severity differed significantly for helmet-wearing and non-helmet-wearing motorcyclists.…”
Section: Summary and Critique Of The Literaturementioning
confidence: 99%
“…According to statistics, in low-income countries, trauma is one of the most important public health concerns. 1 Abdominal traumas accounts for 15% – 20% of all deaths caused by trauma, which can be either premature (caused by bleeding) or late (caused by infection). 2 Besides, blunt abdominal trauma (BAT) is responsible for nearly 80% of all abdominal injuries, resulting in serious morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In Austria, fatal injuries due to motorcycle accidents contributed 20.69% (90) to the number of fatal injuries in 2014 (430), and 22.42% in 2013 [3]. Yasin et al [4] investigated death rates in 2-3-wheelers and found that global mortality increased by a relative ratio of 1.36 over the last decade, which was related to the increased vehicle-to-person ratio and economic inequity. In their study, Ijaz et al [5] determine the most important risk factors associated with the severity of motorcyclists' injuries using the logit model with random parameters.…”
Section: Introductionmentioning
confidence: 99%